Limiting age for the Provo shoreline of Lake Bonneville. (11th November 2015) - Miller, David M.; Wahl, David B.; McGeehin, John P.; Rosario, Jose; Oviatt, Charles G.; Anderson, Lysanna; Presnetsova, Liubov
Abstract: Pluvial Lake Bonneville features a prominent shoreline at the Provo level, which has been interpreted as having formed during a period of threshold-stabilized overflow. The timing of Provo shoreline development is important for paleoclimate interpretations and for inferences on geomorphic process rates. Estimates for the timing of the shoreline formation, based on radiocarbon measurements from gastropod shells, are from approximately 18 to 15 cal ka. One key radiocarbon age on plant fragments from Swan Lake, which formed in the threshold spillway after overflow ceased, has been taken as a young limiting age. The conventional age of 12090 ± 300 14 C when calibrated at 2σ has large uncertainty (13375–15103 cal BP). We report six new AMS radiocarbon ages recovered from new Swan Lake sediment cores. A twig near the base of lacustrine muds was dated at 11, 615 ± 40 14 C yr (13, 350 to 13, 560 cal BP). Age determinations on roots in that interval and deeper in the core are somewhat younger. These ages limit the last overflow of the Provo stand to earlier than ∼13.5 cal ka BP, consistent with the younger bound of the imprecise age reported by Bright. If conservative interpretations of sedimentation rates for the thick well-sorted sand interval below the lacustrine muds are correct and landscape change that resulted in damming of Swan Lake is accounted for, cessation of flow probably occurred before ∼14.5 cal ka BP.